Islamic Teaching for Generation Z: Inclusive and Creative Approaches in the Book "Islam for Gen-Z" - Nur Habibah, Eka Putri; Iksan, Iksan (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the inclusive and creative approach in Islamic education for Generation Z based on the book Islam for Gen-Z by Hatim Gazali. The method used is qualitative research with a content analysis approach and literature review. This study found that Generation Z, who live in the digital and diversity era, understand religious teachings better through an open and interactive approach. Inclusive education allows students to be actively involved, respect differences in views, and appreciate Islamic values such as justice, tolerance, and equality. In addition, the use of digital technology, such as social media, supports student engagement and makes learning more relevant. The results of the study indicate that the inclusive approach is effective in deepening religious understanding in Generation Z, despite challenges, such as conservative resistance and the need to improve educator skills